Disaster Risk Reduction Literacy Through Participatory Mapping of Tsunami Disaster in Bobanehena - Amelia, Risky; Salim, Astuti; Wahyu Ningrum, Rohima; Aswan, Marwis (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
Halmahera Island in North Maluku consists of active faults that cause frequent tectonic earthquakes. In addition to earthquakes, tsunamis can also occur. Bobanehena village is one of the villages located on the coast of Jailolo sub-district and could be at great risk of a tsunami if an earthquake strikes Halmahera Island. The problems addressed are first, the limited capacity of individuals, households and communities in facing and dealing with tsunami disasters. Second, there is no tsunami evacuation route in Bobanehena Village based on participatory mapping. The method in this service is the Community Based Disaster Risk Reduction (CBDRR) approach which involves the community to be actively involved in disaster management. Participatory mapping of evacuation routes was carried out by Forum Group Discussion (FGD) and assessment of disaster capacity was carried out by submitting pre-test and post-test questionnaires conducted during the activity. The results of the service were a participatory map of the tsunami evacuation route plan and increased community capacity regarding tsunami disasters in Bobanehena Village.